Prevalence and Incidence of Carpal Tunnel Syndrome in Us Working Populations: Pooled Analysis of Six Prospective Studies - Dale, Ann Marie; Harris-Adamson, Carisa; Rempel, David; Gerr, Fred; Hegmann, Kurt; Silverstein, Barbara; Burt, Susan; Garg, Arun; Kapellusch, Jay; Merlino, Linda; Thiese, Matthew S; Eisen, Ellen A; et al. (Scandinavian Journal of Work, Environment ＆ Health, 2013)
Objectives Most studies of carpal tunnel syndrome (CTS) incidence and prevalence among workers have been limited by small sample sizes or restricted to a small subset of jobs. We established a common CTS case definition and then pooled CTS prevalence and incidence data across six prospective studies of musculoskeletal outcomes to measure CTS frequency and allow better studies of etiology. Methods Six research groups collected prospective data at >50 workplaces including symptoms characteristic of CTS and electrodiagnostic studies (EDS) of the median and ulnar nerves across the dominant wrist. While study designs and the timing of data collection varied across groups, we were able to create a common CTS case definition incorporating both symptoms and EDS results from data that were collected in all studies. Results At the time of enrollment, 7.8% of 4321 subjects met our case definition and were considered prevalent cases of CTS. During 8833 person-years of follow-up, an additional 204 subjects met the CTS case definition for an overall incidence rate of 2.3 CTS cases per 100 person-years. Conclusions Both prevalent and incident CTS were common in data pooled across multiple studies and sites. The large number of incident cases in this prospective study provides adequate power for future exposure— response analyses to identify work- and non-work-related risk factors for CTS. The prospective nature allows determination of the temporal relations necessary for causal inference.